2023
DOI: 10.1021/acs.organomet.3c00059
|View full text |Cite
|
Sign up to set email alerts
|

Convenient One-Pot Synthesis of L2Pd(0) Complexes for Cross-Coupling Catalysis

Abstract: A convenient one-pot synthesis of (tBu 3 P) 2 Pd(0) was successfully carried out by using various air-stable Pd(II) salts, such as Pd(cod)Cl 2 , Pd(nbd)Cl 2 , Pd(CH 3 CN) 2 Cl 2 , or Pd(PhCN) 2 Cl 2 , without the use of an external reducing agent. Using Pd(cod)Cl 2 as the precursor, large-scale synthesis of (tBu 3 P) 2 Pd(0) was accomplished in excellent yield and purity. Another protocol was also developed for L 2 Pd(0) complexes via an atom economical one-pot method by reacting in situ generated LPd(R-allyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…30 More recent reports demonstrated that similar Pd( ii )-to-Pd(0) transformations are also possible with the more stable and easier-to-access [PdL(Cl)(η 3 -allyl)] complexes (allyl = various π-coordinated allyl ligands, including cyclic ones, L = phosphine or NHC ligands). 31…”
Section: Resultsmentioning
confidence: 99%
“…30 More recent reports demonstrated that similar Pd( ii )-to-Pd(0) transformations are also possible with the more stable and easier-to-access [PdL(Cl)(η 3 -allyl)] complexes (allyl = various π-coordinated allyl ligands, including cyclic ones, L = phosphine or NHC ligands). 31…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the ligand or capping agent on the metal particles affects the process cost. Traditionally, Pd nanoparticle-catalyzed reactions used phosphine or nitrogen-based ligands. However, the use of ligands can be avoided if the amphiphile PS-750-M has a greater tendency to bind to the metal through carbonyl groups. Nevertheless, carrying out ligand-free nanocatalysis can be challenging as nanoparticle agglomerates, which can lead to poor activity.…”
Section: Design and Applications Of Ps-750-mmentioning
confidence: 99%
“…This is either achieved through reduction of a Pd(II) precursor, or by directly using a Pd(0) precursor. There are many prior examples of Pd(II) sources and precatalysts, whereas Pd(0) precursors are less common. Key examples of Pd(0) sources for cross-coupling catalysis include Pd 2 dba 3 (and its crystalline solvates) for in situ generation, ,, and homoleptic Pd(PR 3 ) n complexes, including Pd(PPh 3 ) 4 , as single-component catalysts (Figure A). , …”
Section: Introductionmentioning
confidence: 99%